The United Nations and Russia's Aggression against Ukraine – Success or Failure? - Dudášová, Simona; Eberle, Jakub; Kočí, Kateřina; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
The United Nations (UN) was founded in 1945 to maintain international peace and security, promote human rights, and provide a forum for member states to cooperate on international issues. Created in the aftermath of the Second World War, the UN, through international cooperation, should prevent similar deadly international conflicts, aligning closely with the principles of liberal institutional theory. However, its effectiveness has been the subject of much debate over the years of the inability to act due to countries’ selfish interests and institutional deadlocks. The ongoing Russian aggression against Ukraine has highlighted some of the limitations of the UN's ability to prevent and resolve conflicts and has raised questions about the organisation's relevance in the 21st century. The following study analyses the role of the United Nations in Russia’s full-scale invasion of Ukraine, assessing its limitations and contributions. By evaluating its actions in addressing the crisis in reference to its original liberal institutional principles and purposes, this thesis seeks to answer the following question: Was the UN's reaction to Russian aggression in Ukraine a success or a failure? This case study contributes to the larger discussions about the contemporary relevance of the United Nations.
Vedoucí práce: Jakub Eberle
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní studia a diplomacie [obor dipl. práce]; diplomové práce; master's theses